Assessing and initiating collaborative governance for sustainable geotourism development: A case study of Maros-Pangkep Geopark in Indonesia - Dwipati, Ummul; Ibrahim, Muh Akmal; Abdullah, Muh Tang (Edelweiss Applied Science and Technology, 2025)
Collaborative governance has emerged as a promising approach for managing complex issues, such as developing geotourism in geoparks. This study examines the application of collaborative governance in the development of Maros-Pangkep Geopark in South Sulawesi, Indonesia, with a focus on the assessment and initiation stages. Through a qualitative descriptive approach, data were collected from in-depth interviews with key stakeholders, including government agencies, academia, the private sector, local communities, and media. The findings reveal that the assessment stage involves evaluating the need for collaboration, identifying key actors, and determining effective collaboration strategies. The Maros-Pangkep Geopark Management Agency plays a central role in coordinating diverse stakeholders and aligning their contributions based on expertise. In the initiation stage, identifying and managing resources, establishing a clear governance structure, and building stakeholder capacity are crucial for successful collaboration. The study highlights the importance of conducting stakeholder analysis, setting shared goals, assessing legal and institutional frameworks, developing sustainable financing mechanisms, and fostering regular communication and coordination among stakeholders. Recommendations include implementing adaptive co-management approaches and strengthening existing collaborative initiatives to support Maros-Pangkep Geopark's nomination as a UNESCO Global Geopark and promote sustainable geopark management that integrates conservation, education, and local economic development through geotourism.